THE IDEOLOGY AND THE IDEATIONAL MEANING PROCESSES BEHIND THE ADVERTISEMENTS OF COSMOPOLITAN MAGAZINE - Cicilia San San; Henny Hartono; Angelika Ryandari (Soegijapranata Catholic University, 2007)
This study tried to reveal the ideology and the process of ideational meaning behind the advertisements found in a female magazine, Cosmopolitan. The analysis of ideology was based on four basic assumptions. They are beauty, prestige, health and others. In analyzing the processes of the ideational meaning, the writer used Halliday theory that discusses about six types of processes. They are material (doing/event) process , mental (thinking/sensing/feeling) process,relational (attributive/identifying) process, behavioral process, verbal process and existential process. The results show that the advertisements are dominated by beauty ideology (45,5%) and relational process (41,4%). Based on the result, it is clear that as a female magazine, Cosmopolitan presents advertisements that offer beauty products/services. Moreover, relational process (identifying) is used more because the producer and the advertiser are aware that they cannot compel the consumers to buy the products/ services offered. The use of the process is aimed to show the products/ services that will raise the curiosity of the consumers and to persuade the consumers to buy the products/services.